Numerical Biomechanics Models of the Interaction Between a Novel Transcatheter Mitral Valve Device and the Subvalvular Apparatus. Issue 4 (July 2021) - Marom, Gil; Plitman Mayo, Romina; Again, Nadav; Raanani, Ehud
Objective: Mitral valve regurgitation (MR) is a common valvular heart disease where improper closing causes leakage. Currently, no transcatheter mitral valve device is commercially available. Raanani (co-author) and colleagues have previously proposed a unique rotational implantation, ensuring anchoring by metallic arms that pull the chordae tendineae. This technique is now being implemented in a novel device design. The aim of this study is to quantify the rotational implantation effect on the mitral annulus kinematics and on the stresses in the chordae and papillary muscles. Methods: Finite element analysis of the rotational step of the implantation in a whole heart model is employed to compare 5 arm designs with varying diameters (25.9 mm to 32.4 mm) and rotation angles (up to 140°). The arm rotation that grabs the chordae was modeled when the valve was in systolic configuration. Results: An increase in the rotation angle results in reduced mitral annulus perimeters. Larger rotation angles led to higher chordae stresses with the 29.8 mm experiencing the maximum stresses. The calculated chordae stresses suggest that arm diameter should be <27.8 mm and the rotation angle <120°. Conclusions: The upper limit of this diameter range is preferred in order to reduce the stresses in the papillary muscles while grabbing more chords. The findings of this study can help improving the design and performance of this unique device and procedural technique.